Fitodisponibilidade de metais utilizando ácidos orgânicos após sucessiva aplicação de resíduos no solo - Silva, Maria A. G. Da; Büll, Leonardo Theodoro [UNESP]; Miggiolaro, Alessandra E. [UNESP]; Antonangelo, João A. [UNESP]; Muniz, Antonio S. (Departamento de Engenharia Agrícola - UFCG, 2014)
The experiment was conducted in order to evaluate the concentration of heavy metals in the soil, from organic residues, extracted by organic acids commonly present in the rhizosphere of the plants and also the occurrence of heavy metal phytotoxicity problems in soybeans grown successively after the use of waste from urban, such as biodigested (LB) and centrifuged sewage sludge (LC), industrial steel slag (E) and lime mud (LCal) that were applied over a long period of time. The experiment was conducted in a Red distrophic Latosol (Oxisol), at UNESP in Botucatu, SP. It consisted of four types of waste, applied at zero (control), 2, 4 and 8 Mg ha-1 (dry basis) before the soybean sowing, every two years, since 2002 till 2010, totaling four applications. In the depth analysed, 0 to 0.10 m and 0.10 to 0.20 m, it was evident that the residue which added most metals to the soil, the leaves and the soybean grains was the LB, increasing the Ni, Cd, Pb and Zn concentration, while in the treatment where the steel slag (E) was used, Cr was the main metal released in the soil. The application of lime mud (LCal) did not increase the concentration of metals in the soil. The soybean crop showed concentration of Cr, Ni and Zn, exceeding the maximum permitted limit for food grains, when it received LB, especially in the highest dose of 8.0 Mg ha-1.

Conduziu-se este estudo com o objetivo de avaliar a concentração de metais pesados no solo, provenientes de resíduos orgânicos, bem como a ocorrência de fitotoxicidade de metais em soja. Os metais no solo foram extraídos por ácidos orgânicos, comumente presentes na rizosfera das plantas. A soja foi cultivada sucessivamente, durante oito anos, e recebeu repetidamente, a aplicação dos resíduos de origem urbana, como lodo de esgoto biodigerido (LB) e lodo de esgoto centrifugado (LC), e de origem industrial, como escória de aciaria (E) e a lama cal (LCal). O experimento foi conduzido em Latossolo Vermelho distrófico (Oxisolo) na UNESP, Botucatu, SP, onde recebeu os resíduos nas doses de zero (controle) 2, 4, e 8 Mg ha-1, antes da semeadura da soja, de 2002 a 2010, a cada dois anos, totalizando quatro aplicações. Nas profundidades analisadas de 0 a 0,10 m e de 0,10 a 0,20 m, ficou evidente que o resíduo que mais acrescentou metais ao solo e às folhas e grãos da soja, foi o LB, aumentando a concentração de Ni, Cd, Pb e Zn, enquanto que nos tratamentos em que se aplicou a escória (E), o principal metal liberado ao solo foi o Cr. A aplicação da LCal não aumentou a concentração dos metais e a soja apresentou uma concentração de Cr, Ni e Zn acima dos limites máximos permitidos para grãos alimentícios, quando recebeu LB, principalmente na dose de 8,0 Mg ha-1.
Bioavailability of metals using organic acids after successive application of residues in soil
Keywords: lodo de esgoto; escória de aciaria; lama cal; Glycine max; biodigested sewage sludge; centrifuged sewage sludge; steel slag and lime mud; Glycine max